Management of Chemicals and Hazardous Waste in Environmental Engineering Laboratory Rajamangala University of Technology Suvarnabhumi - Manokhun, Pitiporn; Thiamngoen, Phattharamat (Journal of Applied Research on Science and Technology (JARST), 2020)
Chemicals are used in studies, experiments, and research from the laboratory called chemical wastes, that may be in the form of solids, liquids, or gases. In case of improper handling, these wastes probably affect human health and contaminate the environment. This project was studied at the environmental engineering laboratories of the Rajamangala University of Technology Suvarnabhumi. The purpose of this project is to create a management system for chemicals and hazardous wastes from laboratories, and to evaluate the knowledge of students who are laboratory users. This study can be divided into 3 parts that are chemical management in the laboratory, hazardous waste management, and prevention of hazards in the laboratory. The information systems and chemical storage platform using the GHS systems (Globally Harmonized System for Classification and Labeling of Chemicals) were investigated and were able to classify the 3 types of chemicals according to hazards in the laboratory that were physical hazards, health hazards, and environmental hazards. For chemical waste management, the studied laboratory generated hazardous liquid wastes which were collected into corrosion-resistant containers, and hazardous solid wastes were managed by preparing a suitable container in order to collect wastes during waiting for appropriate disposal. The aspect of safety and prevention of the hazards in laboratories was developed the media to communicate to all laboratory users that are signboard and video regarding to hazard types, chemical waste types, and laboratory safety. The researcher evaluated the comprehension of 48 students by conducting pre-test and post-test in 3 studied parts. The results showed that students had more knowledge in all aspects. The increase of knowledge for chemical management in the laboratory, hazardous waste management, and prevention of hazards in the laboratory was 36%, 27%, and 24, respectively. This obviously indicates that the students understand the laboratory management system, which leads to use the laboratory much more correctly and safely.